2001
DOI: 10.1002/ana.1134
|View full text |Cite
|
Sign up to set email alerts
|

Human apolipoprotein E4 accelerates β‐amyloid deposition in APPsw transgenic mouse brain

Abstract: The human apolipoprotein E4 (ApoE4) isoform is associated with genetic risk for Alzheimer's disease. To assess the effects of different ApoE isoforms on amyloid plaque formation, human ApoE3 and ApoE4 were expressed in the brains of transgenic mice under the control of the human transferrin promoter. Mice were crossed with transgenic mice expressing human amyloid precursor protein containing the Swedish mutation (APPsw), which facilitates amyloid beta peptide (A beta) production. The following progeny were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…The findings that apoE4 stimulates deposition of A␤ and apoE deficiency blocks formation of fibrillar A␤ deposits are in accordance with and extend previous studies with APP ϫ apoE doubletransgenic mice and with APP-transgenic mice on a null apoE mouse background (24,36,39,42,43). Formation of A␤ deposits did not require apoE, but it was accelerated significantly and in an isoform-specific fashion by apoE4 (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…The findings that apoE4 stimulates deposition of A␤ and apoE deficiency blocks formation of fibrillar A␤ deposits are in accordance with and extend previous studies with APP ϫ apoE doubletransgenic mice and with APP-transgenic mice on a null apoE mouse background (24,36,39,42,43). Formation of A␤ deposits did not require apoE, but it was accelerated significantly and in an isoform-specific fashion by apoE4 (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are in line with a study demonstrating promotion of parenchymal and vascular amyloid by human ApoE4, without affecting the metabolism of APP. 19 We conclude that any modulation of the amyloid pathology by ApoE4 must be ascribed to postsynthetic events, taking place after the amyloid peptides are excised from APP as a consequence of intra-or extracellular interaction with ApoE4 lipoproteins that slow down clearance and degradation of A␤. Moreover, we demonstrate that the cellular origin of ApoE4 plays an important role in determining the fate of the amyloid peptides.…”
Section: Cellular Mechanisms Involved In Neuronal Versus Glial Apoe4mentioning
confidence: 85%
“…13,16,17 Another study demonstrated, however, that expression of human ApoE4 but not of ApoE3, both under control of the transferrin gene promoter, accelerated deposition of amyloid in APP/Swe transgenic mice. 19 In a similar study, overexpression of either ApoE isoform under control of the prion gene promoter neither accelerated nor increased the amyloid burden, nor markedly affected the metabolism before amyloid deposition even in the presence of mutant presenilin-1 in tripletransgenic mice. 20 In addition to parenchymal amyloid plaques, the vascular deposits presenting as cerebral congophilic amyloid angiopathy (CAA) are a major pathological sign in AD 21 with a prevalence of more than 90% in the oldest patients.…”
mentioning
confidence: 89%
“…Given that the stimulus for amyloid processing and deposition is different between these two experimental systems, a direct comparison is not possible. Non-transgenic BALB/c mice typically do not develop amyloid pathology [8,10], however following experimental induction, these mice developed deposits consisting solely of mouse amyloid. Mouse A␤ is highly homologous to human A␤ [15,20], but typically does not deposit into plaques.…”
Section: Experimental Models Of Admentioning
confidence: 99%